People and Things - Skibo, James M. author. aut Link
XIII, 170 p. 16 illus.
Keywords: People and Things: A Behavioral Approach to Material Culture James M. Skibo, Department of Anthropology, University of Illinois, Normal, IL Michael B. Schiffer, Department of Anthropology, University of Arizona, Tucson, AZ The core of archaeology is the relationship between people and things. Left without informants and, in many cases, textual data, archaeologists strive to reconstruct past life through the window of artifacts: things made, used, and modified by individuals while participating in the activities of everyday life. According to behavioral archaeologists, our ability to understand the relationship between people and things in the present is the foundation for archaeological reconstruction of the past. This comprehensive text sets forth a theory for understanding the relationship between people and things. Humans, whether in the distant past or in our current world, make choices while inventing, developing, replicating, adopting, and using their technologies. A wide arc of factors, from utilitarian to social and religious can affect these choices. The theoretical model presented here provides the means to understand how people, whether it be Paleolithic stone tool makers or 21st century computer designers and users, negotiate these myriad factors throughout the artifact’s life history. While setting forth a behavioral theory, the book also engages the ideas of other competing theories, focusing especially on agency, practice, and selectionism. Six case studies form the core of the book, and provide clear examples of how the theory can be applied to a range of artifacts and people from prehistoric North American ball courts and smudge pits to the first electric cars and 19th century electromagnetic telegraph technologies. This book provides the reader, for the first time between two covers, a wide array of examples that can guide their own work. Archaeology and anthropology graduate students will find this book of interest. Twenty years in the making, this work will be an essential tool for new scholars as well as experienced members in the field of archaeology or any researcher who investigates technology.